Junction‐Free Electrospun Ag Fiber Electrodes for Flexible Organic Light‐Emitting Diodes. Issue 7 (28th December 2017) - Choi, Junhee; Shim, Yong Sub; Park, Cheol Hwee; Hwang, Ha; Kwack, Jin Ho; Lee, Dong Jun; Park, Young Wook; Ju, Byeong‐Kwon
Abstract: Fabrication of junction‐free Ag fiber electrodes for flexible organic light‐emitting diodes (OLEDs) is demonstrated. The junction‐free Ag fiber electrodes are fabricated by electrospun polymer fibers used as an etch mask and wet etching of Ag thin film. This process facilitates surface roughness control, which is important in transparent electrodes based on metal wires to prevent electrical instability of the OLEDs. The transmittance and resistance of Ag fiber electrodes can be independently adjusted by controlling spinning time and Ag deposition thickness. The Ag fiber electrode shows a transmittance of 91.8% (at 550 nm) at a sheet resistance of 22.3 Ω □ −1, leading to the highest OLED efficiency. In addition, Ag fiber electrodes exhibit excellent mechanical durability, as shown by measuring the change in resistance under repeatable mechanical bending and various bending radii. The OLEDs with Ag fiber electrodes on a flexible substrate are successfully fabricated, and the OLEDs show an enhancement of EQE (≈19%) compared to commercial indium tin oxide electrodes. Abstract : The fabrication of junction‐free electrospun Ag fiber electrodes for organic light‐emitting diodes (OLEDs) is proposed. They show excellent performance compared to indium tin oxide (ITO) in respect of transparency and resistance. In addition, surface roughness, which is a serious problem in metal‐based flexible transparent electrodes for OLED, is controllable. OLEDs with a junction‐free electrospun Ag fiber electrode exhibit a higher external quantum efficiency than using an ITO electrode.